New insights into the heterogeneity of Th17 subsets contributing to HIV-1 persistence during antiretroviral therapy. Issue 1 (December 2016) - Wacleche, Vanessa; Goulet, Jean-Philippe; Gosselin, Annie; Monteiro, Patricia; Soudeyns, Hugo; Fromentin, Rémi; Jenabian, Mohammad-Ali; Vartanian, Shant; Deeks, Steven; Chomont, Nicolas; Routy, Jean-Pierre; Ancuta, Petronela
Abstract Background Th17 cells are permissive to HIV-1 infection and their depletion from the gut of infected individuals leads to microbial translocation, a major cause for non-AIDS co-morbidities. Most recent evidence supports the contribution of long-lived Th17 cells to HIV persistence during antiretroviral therapy (ART). However, the identity of long-lived Th17 cells remains unknown. Results Here, we performed an in-depth transcriptional and functional characterization of four distinct Th17 subsets and investigated their contribution to HIV reservoir persistence during ART. In addition to the previously characterized CCR6+ CCR4+ (Th17) and CCR6+ CXCR3+ (Th1Th17) subsets, we reveal the existence of two novel CCR6+ subsets, lacking (double negative, CCR6+ DN) or co-expressing CXCR3 and CCR4 (double positive, CCR6+ DP). The four subsets shared multiple Th17-polarization markers, a fraction of cells proliferated in response toC. albicans, and exhibited lineage commitment and plasticity when cultured under Th17 and Th1 conditions, respectively. Of note, fractions of CCR6+ DN and Th17 demonstrated stable Th17-lineage commitment under Th1-polarization conditions. Among the four subsets, CCR6+ DN expressed a unique transcriptional signature indicative of early Th17 development (IL-17F, STAT3), lymph-node homing (CCR7, CD62L), follicular help (CXCR5, BCL6, ASCL2), and self-renewal (LEFI, MYC, TERC). Cross sectional and longitudinal studies demonstrated that CCR6+ DN cells were the most predominant CCR6+ subset in the blood before and after ART initiation; high frequencies of these cells were similarly observed in inguinal lymph nodes of individuals receiving long-term ART. Importantly, replication competent HIV was isolated from CCR6+ DN of ART-treated individuals. Conclusions Together, these results provide new insights into the functional heterogeneity of Th17-polarized CCR6+ CD4+ T-cells and support the major contribution of CCR6+ DN cells to HIV persistence during ART.